INVESTIGATING STUDENTS’ CHALLENGGES IN WRITING DESCRIPTIVE TEXTS - Sugianto (Journal of English Education and Literature, 2025)
The study aimed to assess students' writing skills and identify the challenges they faced in writing descriptive texts. Using a case study approach, the research followed a descriptive qualitative method. The participants were 28 second-year students from MA NW Nabi’ Nubu’. The research employed writing tests and interviews as data collection tools. The findings revealed that the average score of the students was 69.92, indicating that their ability to write descriptive texts was relatively low. Three students (12%) scored below 60, placing them in the "poor" category, while ten students (40%) scored between 61-70, also categorized as poor. Nine students (36%) scored between 71-80, which was considered "average," and three students (12%) received scores in the "very good" range. When analyzing their performance in specific writing aspects, vocabulary and organization were rated as "good to average," while content, grammar, and mechanics were categorized as "fair to poor." In conclusion, the study found that students struggled most with grammar, content, and mechanics. It is recommended that English teachers provide more practice in writing to help improve these areas, particularly content and grammar, when writing descriptive texts.